Productive performance of pure breeds and cross-bred goat genotypes in southern Tunisia - Gaddour A.; Najari S.; Ouni M. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
The study aim was to establish meat and dairy performance of local goats, some breeds and cross-bred groups under an oasis management mode in southern Tunisian. A large data set, collected from 1980 to 1996, was used to analyse the phenotypic potential of the genotypes. Periodic individual controls were used to estimate kids-goat weight at some standard ages and dairy performance such as, daily milk average, total production by lactation and milking period of the goat's genetic groups under study. Statistical analyses of about 1928 kids-goat weights and 1923 individual goat milking showed that cross-breeding allowed growth performance to be improved from the first generation compared to the production of the local population. The Alpine*local goat cross showed the greatest potential. Kid weight increased on average about 125% at 120 days of age. The performance of all imported genotypes seems to be lower than those known in their original areas.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)